Centers for optimizing water management in agroecosystems & global food security - Ondrasek, Gabrijel; Rengel, Zed (Frontiers in Sustainable Food Systems, 2024)
Global food security (GFS) is challenged by increasing food demand due to population growth and climate change. International trade and globalization have underpinned GFS until the most recent public health, geopolitical and economic crises, when virtually overnight, the focus of governments has shifted towards domestically and locally produced foods. However, the agri-food sector has limited flexibility, and relatively long periods are needed for fundamental/sustainable changes. One of the crucial factors enabling GFS is the efficient water management, but the required knowledge and capabilities are often lacking regionally/locally. We propose the Centers for Optimizing Water Management in Agroecosystems as a long-term solution. The Centers would be the specialized hubs for promotion of research, innovation and technology transfer, raising the knowledge of stakeholders (farmers, extension and government officials, scholars, students, policymakers and other professionals) and their capacities in water management. These Centers would operate as research/education/technology demonstration entities tailored to the specifics of a particular country/region, aiming to address the most important and pertinent goals and outcomes with a highspatial-resolution outreach. Finally, the Centers will improve farmers' livelihoods, contribute to sustainable and efficient use of agro-environmental resources, and increase productivity and food quality, ultimately supporting GFS.